Feasibility of Percutaneous Robot-Assisted Epiduroscopic System - Shin, Dong Ah; Kim, Chunwoo; Yudoyono, Farid; Yun, Yeomin; Ha, Yoon; Kang, Sungchul (American Society of Interventional Pain Physicians, 2018)
Background: Endoscopy has replaced open surgery, especially in spinal surgery. Among them, image-guided epiduroscopy allows pain generators to be identified, including epidural adhesion, fibrotic tissues, root compression, and spinal stenosis. However, the heavy lead apron worn by pain physicians to avoid exposure to radiation can induce occupational hazards, such as orthopedic complications and radiation-induced cancer. Hence, we developed a robotic system to address these problems. Objective: The aim of the study was to evaluate the feasibility of a robot-controlled epiduroscopic system. Study Design: In vivo animal experiment. Setting: University in Republic of Korea. Methods: The robot-controlled epiduroscopic system was developed using the open architecture robot system (The Raven Surgical Robotic System, CITRIS, Berkley, CA, USA). The robotic system consists of a lab-made epiduroscope, steering section, robotic arm, and manipulator. For the in vivo study, 2 Yorkshire pigs were used to simulate an epiduroscopic procedure with the robotic system. Results: The insertion and steering of the catheter was performed safely, and epiduroscopic visualization was obtained without side effects. There were no device-related complications. Radiation exposure for the primary operator was 80% lower than the levels found during conventional epiduroscopic procedures. All live pigs showed normal behavior without any signs of pain. The mean time to reach the target region was less than 8 minutes. Limitations: The epiduroscopic procedure was performed on pigs and not on humans. The dimensions of the spinal canal of pigs cannot compare to those of humans. Conclusions: We demonstrated the feasibility of the robot-assisted epiduroscopic system.